Anemia Is Associated With Poor Clinical Outcomes in Hospitalized Patients With Takotsubo Cardiomyopathy. (October 2021) - Lu, Xiaojia; Li, Pengyang; Teng, Catherine; Cai, Peng; Wang, Bin
The association between anemia and Takotsubo cardiomyopathy (TCM) has not been well studied. To assess the effect of anemia on patients hospitalized with TCM, we identified 4733 patients with a primary diagnosis of TCM from the 2016 to 2018 National Inpatient Sample (NIS) database (the United States) using the International Classification of Diseases, 10th edition, Clinical Modification ( ICD-10-CM ) code. Of these, 603 (12.7%) patients had a comorbidity of anemia and 4130 did not. After propensity score matching, we compared the in-hospital outcomes between the 2 groups (anemia vs nonanemia, n = 594 vs 1137). Patients with TCM with anemia had significantly higher rates of in-hospital complications, including cardiogenic shock (11.4% vs 4.0%, P < .001), ventricular arrhythmia (6.6% vs 3.6%, P = .008), acute kidney injury (22.7% vs 13.1%, P < .001), acute respiratory failure (22.6% vs 13.1%, P < .001), longer length of hospital stay (5.6 ± 5.8 days vs 3.6 ± 3.6 days, P < .001), and higher total charges (US79 586 ± 10 2436 vs US50 711 ± 42 639, P < .001). In conclusion, patients with anemia who were admitted for TCM were associated with a higher incidence of in-hospital complications compared with those without anemia.